2011
DOI: 10.1007/s10531-011-0070-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevational patterns of species richness and density of rattan palms (Arecaceae: Calamoideae) in Central Sulawesi, Indonesia

Abstract: We studied species richness and density of rattan palms in 50 plots of 10 9 100 m 2 each between 250 m and 2420 m in eight sites in Lore Lindu National Park (LLNP), Central Sulawesi. Rattans were observed in all sample sites, representing three genera and 34 species. The elevational patterns for species richness and density were humped-shaped with maxima around 1000 m. Polynomial models of second order explained 59 and 32% of species richness and density with the factor elevation, respectively. A majority of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 50 publications
1
19
0
2
Order By: Relevance
“…, and mature (13 stems) ( Figure 4c) rattan ( Figure 4d). The number of individualsfor mature rattan species C.zollingeri (13 stems) stages study area was lower compared to the study on other sites in Dampelas Sojol Subdistrict Donggala Regency (Kunut et al 2014),the location within Taman Nasional Lore Lindu (LLNP), and outside of LLNP, C. zollingeri (645 individu) (Stiegel et al 2011) andcompared to the research results in Papalia Protected Forest, Konawe Selatan District, C.zollingeri found more than 40 stems (Uslinawaty et al 2014). In Dampelas Sojol Subdistrict, Donggala Regency, other rattan species was found, namely rotan cacing (C. melanoloma Martius), lambang (C. ornatus), tohiti (C. inops), and noko (C. koordersianus).…”
Section: Population Ofmentioning
confidence: 57%
“…, and mature (13 stems) ( Figure 4c) rattan ( Figure 4d). The number of individualsfor mature rattan species C.zollingeri (13 stems) stages study area was lower compared to the study on other sites in Dampelas Sojol Subdistrict Donggala Regency (Kunut et al 2014),the location within Taman Nasional Lore Lindu (LLNP), and outside of LLNP, C. zollingeri (645 individu) (Stiegel et al 2011) andcompared to the research results in Papalia Protected Forest, Konawe Selatan District, C.zollingeri found more than 40 stems (Uslinawaty et al 2014). In Dampelas Sojol Subdistrict, Donggala Regency, other rattan species was found, namely rotan cacing (C. melanoloma Martius), lambang (C. ornatus), tohiti (C. inops), and noko (C. koordersianus).…”
Section: Population Ofmentioning
confidence: 57%
“…A study of the palm flora in two plots in Lore Lindu National Park in Central Sulawesi conducted by Mogea (2002) reported 20 species of Calamus, 16 of which were unidentifiable. In a more detailed study, Stiegel et al (2011) found 33 species of Calamus in Lore Lindu National Park, 24 of which they were unable to identify. In another National Park in south-eastern Sulawesi, Powling (2009) recorded 19 species of Calamus, two of which he was unable to identify.…”
Section: Introductionmentioning
confidence: 97%
“…(Stiegel et al, 2011;Svenning et al, 2008). Multi-stemmed palms (clonal palms) are particularly important economically in local communities in the tropics where they are used for palm heart and rattan production (Balick 1990;.…”
Section: Discussionmentioning
confidence: 99%
“…Stiegel, S., Kessler, M., Getto, D., Thonhofer, J., & Siebert, S. F. (2011). Elevational patterns of species richness and density of rattan palms (Arecaceae: Calamoideae) in Central Sulawesi, Indonesia.…”
Section: List Of Referencesmentioning
confidence: 99%
See 1 more Smart Citation